Exploration of smart adherence‐monitoring methods in vitamin D‐deficient patients: A pilot feasibility clinical study - Ki Young Huh; Hwiwon Lee; SeungHwan Lee; Kyung‐Sang Yu; Kyung Hwan Kim; Heejin Kim (Wiley, 2023)
Abstract Treatment adherence is an underestimated determinant of treatment success. Poor treatment adherence can also affect the efficacy of clinical trials. A combination of multiple adherence‐monitoring methods is required to ensure robustness. We investigated whether multiple adherence‐monitoring methods, including a novel smartwatch‐based monitoring method, would yield reliable and concordant results. In this open, randomized, decentralized clinical trial, vitamin D‐deficient individuals were randomized to an App − only group (an electronic medication diary) or an App + Watch group (i.e., App and smartwatch‐based monitoring) groups after a week run‐in period. The participants received vitamin D supplements (1000 IU) for 12 weeks (two consecutive periods of 6 weeks) with two pill counts (at the sixth week) and biweekly blood samplings for serum 25(OH) vitamin D concentration. Adherence was assessed and compared between the methods. Sixteen participants were enrolled, of which 13 completed the study. Serum 25(OH) vitamin D levels comparably increased in both groups until the first 7 weeks but trended higher in the App + Watch group in the second period. The number of doses recorded by the pill count and App did not differ significantly between the run‐in and Period 1 (p = 0.5534) but became significantly discrepant in Period 2 (p = 0.0225). In contrast, the concordance for smartwatch‐based monitoring was consistent in either period (p = 0.5898 and p = 0.5839, respectively). We explored multiple adherence‐monitoring methods in this pilot feasibility clinical study. Smartwatch‐based adherence monitoring may be an objective and sensitive method for measuring treatment adherence.